2014
DOI: 10.1016/j.devcel.2014.09.013
|View full text |Cite
|
Sign up to set email alerts
|

The Chromosome Axis Controls Meiotic Events through a Hierarchical Assembly of HORMA Domain Proteins

Abstract: Summary Proteins of the HORMA domain family play central but poorly understood roles in chromosome organization and dynamics during meiosis. In C. elegans, four such proteins (HIM-3, HTP-1, HTP-2, and HTP-3) have distinct but overlapping functions. Through combined biochemical, structural, and in vivo analysis, we find that these proteins form hierarchical complexes through binding of their HORMA domains to cognate peptides within their partners’ C-terminal tails, analogous to the “safety belt” binding mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
229
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(256 citation statements)
references
References 57 publications
(93 reference statements)
15
229
0
Order By: Relevance
“…We therefore refer to this pair of paralogs as HTP-1/2. In vitro and in vivo experiments have demonstrated that HTP-1/2 are recruited to the chromosome axes through their interaction with closure motifs within the long tail of HTP-3 and at the extreme C terminus of HIM-3 (16). Our aligned and averaged data confirm that HTP-1/2 localize to the chromosome axes at 57.3 ± 1.6 nm off-center (Fig.…”
Section: Averaging Over Many Samples Increases the Precision Of Supersupporting
confidence: 70%
See 4 more Smart Citations
“…We therefore refer to this pair of paralogs as HTP-1/2. In vitro and in vivo experiments have demonstrated that HTP-1/2 are recruited to the chromosome axes through their interaction with closure motifs within the long tail of HTP-3 and at the extreme C terminus of HIM-3 (16). Our aligned and averaged data confirm that HTP-1/2 localize to the chromosome axes at 57.3 ± 1.6 nm off-center (Fig.…”
Section: Averaging Over Many Samples Increases the Precision Of Supersupporting
confidence: 70%
“…This observation indicates that the electron-dense elements that flank the SC may not correspond to assemblies of axis proteins, although some axis proteins appear to localize at or near these structures (22). Although recent work has illuminated some structural details of axis proteins and their interactions (16,(22)(23)(24), the overall organization of the chromosome axis remains largely undetermined.…”
Section: Significancementioning
confidence: 79%
See 3 more Smart Citations